HUBUNGAN INDEKS MASA TUBUH (IMT) DAN TINGKAT STRES DENGAN SIKLUS MENSTRUASI PADA REMAJA PUTRI DI SMK WIDYA UTAMA INDRAMAYU TAHUN 2018 - Ani Nurhaeni; Putri Gayuh Uthami; Tutin Marlia (LPPM ITEKES Mahardika, 2018)
Background:Reproductive health is an important part of the health program. Several diseases that related to the reproductive system are important things to be solved such as irregular menstrual cycles. Some factors that affect the menstrual cycle are the influence of weight, physical activity, and the process of ovulation and adequate luteal function. Now, special attentions arealso emphasized on the diet behavior and stress. The purpose of this study was to know the correlation of Body Mass Index (BMI) and stress level with menstrual cycle of young women in SMK WidyaUtama Indramayu. Methods: The design of this study used an analytic survey using a cross sectional design. The instrument used is the questionnaire of Depression Anxiety Stress Scale (DASS) that has been standardized and modified. questionnaire for measuring the menstrual cycle is a question about the menstrual cycle. Body mass index (BMI) is measured by calculating body weight / TB2 in kg / m2. Result: The results showed that the Body Mass Index in Normal category (68.3%), stress level in the normal category (68.3% and menstrual cycle in the normal category (56.7%). There was a significant relationship between body mass index and cycle menstruation with a value of p = 0.000 There is a significant relationship between stress levels with the menstrual cycle with a value of p = 0.031. Conclusion: that need to be recommended are the need to control the weight so that the nutritional status will be in the ideal level, able to adapt the stress and regularly record the menstrual period in order to control the menstrual cycle.